Intelligent Care Enterprisre: Baby Loves Chair / Phaillevyonne Heryson [et al.] - Heryson, Phaillevyonne; Md Rais, Muhamad Nazarul Hafizi; Mohamad Bakar@Mohd Basri, Nadiah; Mohd Taib, Nur Syafiqah; Azman, Anis Syamimi (2018)
This business is based on partnership which is consists of five members which hold important position in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager, and Financial Manager. This business capital is amount to RM 100,00.00. Our BabyLove chair is for a baby 4 to 36 months and weight less than 15 kg.